Design and development of drill bit sharpening jig for bench grinder - Ali Zulfakar, Khairudin (2016)
This thesis deals with design and development of the drill bit sharpening jigs for bench grinder. The objective of this thesis is to design the drill bit sharpener jig that enhance the better outcome rather than manual sharpening operation. The thesis follows with the development of the drill bit sharpening jig that can be attached to the bench grinder . The structural three-dimensional solid modeling of drill bit sharpening jig was developed using the computer-aided drawing software which is CATIA V5R21. The strategy of validation of the model design was developed. The generative part structural analysis was then performed using simulation in CATIA V5R21 to detect the Von Mises distribution.The design and suitable material will be validated. The fabrication of the jig may undergoes in various machining process such as milling , turning , electrical discharge wirecut and grinding . The assembled part shall be tested on the bench grinder. Besides , several dull drill bits will be sharpen using the jig. These assessment results are significant to improve the component design at the early developing stage.Further analysis will be conducted by testing the drilling process on the workpiece.The resharpen drill bits and the new drill bits will results on the difference surface roughness.Thus, the surface roughness analysis is performed to distinguish hole surface roughness outcomes for both drill bits.The results shows the difference of surface roughness between both hole surface is small and insignificant.Thus, it means that the outcomes is relatively same.The jig can also significantly reduce the cost and time to market, and improve product reliability and customer confidence.